Synaptotagmin1 regulates membrane fusion events that are essential for abiotic stress tolerance in plants - Pérez-Sancho, Jessica; Rosado Rey, Abel; Botella-Mesa, Miguel Ángel (My University, 2013)
Plants undergo continuous exposure to various abiotic stresses in their natural environment. For this reason they have evolved intricate mechanisms to perceive external signals and trigger the physiological changes necessary to adapt and survive under such conditions. The plasma membrane is a physical barrier that separates the intracellular and extracellular environments and its integrity is essential for stress tolerance. Here we present a role for plant synaptotagmins in plasma membrane integrity maintenance through Vesicle-PM fusions. We also evaluate the physiological consequences of the SYT depletion under several abiotic stress conditions
Keywords: Membrana celular vegetal; Synaptotagmin; Plasma membrane; Stress